Quantum illumination assistant with error-correcting codes - Wen-Zhao Zhang; Yu-Han Ma; Jing-Fu Chen; Chang-Pu Sun (New Journal of Physics, 2020)
We scheme how to enhance the detection ability of quantum target recognition without using entanglement resources. Based on the commonly used error-correcting codes and corresponding decoding method, our scheme gives lower error probability and higher signal-to-noise ratio (SNR) in comparison with the conventional entanglement protocols. In addition, we further investigate the interplay between the SNR and the detection efficiency in quantum target recognition. Results show that, they behave a completely reverse trend when increasing the auxiliary dimension. This is an important limiting factor when optimizing the detection process. Under the existing experimental conditions, our protocol has stronger ability to resist environmental noise when keeping a certain SNR and detection efficiency. Our scheme provides a potential platform for further research and implementation of quantum target recognition.